A multi-hop ARQ protocol for underwater acoustic networks - DOYLE, LINDA (IEEE, 2007)
Underwater acoustic networks are envisaged to be the enabling technology for oceanographic data collection, pollution monitoring, offshore exploration and tactical surveillance applications. Unique characteristics of underwater acoustic channels such as large propagation delays and high bit error rates pose a challenge to designing reliable and efficient communication protocols. In this paper, we propose an opportunistic acknowledgement scheme suited for Stop and Wait ARQ protocols and demonstrate using simulations that it achieves better latency and energy efficiency than traditional non-opportunistic schemes for both one and two-dimensional multi-hop acoustic channels.
PUBLISHED
Keywords: 1D multihop acoustic channels 2D multihop acoustic channels acoustic propagation delay automatic repeat request procedure communication protocols high bit error rate multihop ARQ protocol opportunistic acknowledgement scheme stop and wait ARQ protocols underwater acoustic channels underwater acoustic networks